HYDRODYNAMIC STUDIES IN TWO-PHASE STIRRED FLUIDIZED BED WITH THREE TYPES OF IMPELLERS: Original scientific paper - DEEPA PRIYA, N.; SARAVANAN, K. (Chemical Industry & Chemical Engineering Quarterly, 2021)
Fluidized beds are extensively used in petrochemical, chemical process industries, pharmaceutical, food and biotechnology industries. They are preferred to process materials with a wide range of particle size distribution and offer even temperature distribution and excellent heat and mass transfer. To improve the quality of the fluidized bed, mechanical stirring can be employed along with aeration. Hence, an attempt was made to study the hydrodynamics of stirred fluidized bed using air-water system. The characteristics of the fluidized bed can be well understood by studying its hydrodynamics. Pressure drop is one of the vital factors which affect the performance of fluidized bed. Hence, the effects of gas velocity and stirrer speed on pressure drop and power were studied for both stirred and unstirred bed conditions. It was observed that pressure drop and power increases with increase in gas velocity and stirrer speed. Also, the pressure drop and power are lower for the stirred bed condition than the unstirred bed condition.